Green financing in Kazakhstan: current state and prospects - R. D. Doszhan; A. E. Sabidullina; A. Z. Nurmagambetova; A. K. Kozhakhmetova (Экономика: стратегия и практика, 2022)
The purpose of this article is to assess the current state of green finance in Kazakhstan and build proposals for further development. The methodological basis of the scientific article was the general scientific methods of systematization of theoretical data, methods of scientific observation of economic processes, structural-logical and system analysis. Based on the study of the theoretical aspects of green financing and the analysis of structural programs and the legislative framework, the conceptual features of the Kazakh model of green financing were identified. The analysis tool was a statistical study of the financial market of Kazakhstan. A comparative analysis of the state of the green bond market was carried out on the basis of two parameters of the Climate Bond Initiative (CBI) database: the Green bond database of the Climate Bond Initiative (GBDB), the database of social bonds and sustainable development bonds (SSBD). The CBI statistical data formed on the basis of the study due to the fact that this organization determines the rating of green securities and makes a listing of issuers, and is also the main source of collecting and distributing information about green financial instruments on a global scale, especially about green bonds and certification. Statistical data were selected for 2021, as the issue of green securities in Kazakhstan began that year, and the country entered the world system as an accredited member and prospective partner of the global green bond market. The main result is the identification of current global trends in the development of green finance in Kazakhstan. Conclusions were drawn that the study and implementation of best practices in the field of green finance in the republic has been developed thanks to strong state support. The research proposed in the article can assist researchers in formulating research problems related to green finance.